DISEMINASI KEKERASAN MELALUI MEDIA MASSA - Riyanto, Buddy (Transformasi, 2011)
Abstract Â  The increasing violence in our mass media is a hard fact. There are two opinions regarding this issue. The first is the educational practitioner which alarm about the future of the younger generation. They argue that violence will influence the emotional and behavioral aspect of the audience, especially the children. Meanwhile, there are a large number of people which encourage this phenomenon, namely the media violence, because it will increase their profit, politically and economically. In this article, I try to see the issue from different point of view. I will argue that violence has an aesthetic dimension in itself. This argument can explain further, why it is so difficult to erase the violence dimension in the media. Keywords: violence, media, aesthetic dimension.